PENGARUH PENGGUNAAN MEDIA PEMBELAJARAN QUIZIZZ TERHADAP MOTIVASI BELAJAR MAHASISWA STKIP PGRI JOMBANG - Lusianah; Roy Wahyuningsih (JOURNAL SCIENTIFIC OF MANDALIKA (JSM) e-ISSN 2745-5955 | p-ISSN 2809-0543, 2022)
This study aims to determine the effect of the use of Quizizz learning media on the learning motivation of STKIP PGRI Jombang students, based on the results of the study during learning there is interaction between lecturers and students, there are tools to deliver material. The tool is in the form of teaching materials or learning media so that students are motivated to participate in learning. However, in the use of learning media, there are several obstacles as is the case for students sometimes wanting creative and not boring learning. The research method used in this study is a quantitative approach. The type of research used is a type of research ex post facto, namely research that is carried out after an event occurs and looks at the factors that can cause the event. Sampling in this research uses proportional random sampling techniques. Data collection techniques use questionnaires or questionnaires and documentation. Hypothesis testing is carried out by simple linear regression. Based on the results of data analysis that has been obtained by researchers, it proves that the use of Quizizz learning media has a positive and significant effect on learning motivation by the correlation or relationship value (R) which is 0.754. from the output obtained a determination (R Square) of 0.568. which means that the influence of free or independent variables (the use of Quizizz learning media) on bound or dependent variables (student learning motivation) was 56.8% and the remaining was influenced by other variables that were not present in this study.